Electric Charge Characteristics of Biofilms Formed on Various Surfaces - Andi Kurniawan; Yasuaki Fukuda (The Journal of Pure and Applied Chemistry Research, 2016)
Biofilm is predominant habitats of microbes in aquatic environments. Biofilm forms when microbes attach on surfaces and produce extracellular polymeric substances. Biofilm matrix has been showed to have high sorption capacity to accumulate various ions including nutrient ions. The main driving force of the accumulation of the ions is supposed to be an electrostatic interaction between the nutrient and the biofilm polymer. Hence, the understanding of electric charge properties of biofilm polymer is critically important to understand the accumulation process. The present study aimed to investigate the characteristics of electric charge properties of biofilm polymer from biofilms formed on various surfaces (stone, wood, glass bottle, teflon, rubber, and stainless steel). The electric charge properties of biofilm polymers were investigated by measuring the electrophoretic mobility of the biofilms in various pHs (range from pH 2 to pH 9) and titrated HCl and NaOH aqueous solution to the biofilm suspension. The results indicated that biofilm matrices seemed to have both negatively and positively charged sites as a result of ionization of functional groups existed in biofilm polymers. According to the results of this study, there is a universal characteristic of electric charge properties of biofilms regardless of the kind of substrate.